System analysis and testing of the benefits of online learning based on madrasah e-learning on physics subjects at MAN 2 Semarang City - Muhammad Luthfi; Susilawati Susilawati; Arsini Arsini (Universitas Ahmad Dahlan, 2022)
This study aims to analyze the application of online learning systems in Physics subjects and test the usability of online learning systems in Physics subjects at MAN 2 Semarang City. This type of research is descriptive qualitative. Data was collected through interviews, questionnaires, observation, and documentation. The questionnaire was created using the PIECES framework and the USE Questionnaire, modified using google forms. The research results show that implementing online learning based on e-learning madrasah has been well. All aspects, including performance, information, economics, control, efficiency, and service, show good categories. The usability test with the USE Questionnaire shows a good level of Usability or Usability in all aspects. This study indicates that the e-learning system of MAN 2 Semarang City is feasible and good to use for online learning.